Elementary School Learning Management Using a Central Approach - Ayu Meiva Agung Lestari; Tri Widayatsih; Suherman Suherman (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to describe the management, implementation, and supporting and inhibiting factors of the center learning model at SD Negeri 1 Pematang Panggang, Indonesia, during the 2025/2026 academic year. A qualitative approach with a descriptive method was employed, utilizing interviews, observation, and documentation to gather data from 15 teacher respondents implementing the center model. The findings reveal three key aspects. First, the management of learning centers encompasses comprehensive planning, organizing, actuating, and controlling processes, both internally and externally. Second, the implementation is structured around four distinct centers preparation, nature, blocks and creativity, and acting and physical exercise rotated from Monday to Thursday, with Fridays dedicated to thematic culmination activities. Third, evaluation is conducted in a staged manner, including daily, weekly, mid-semester, and end-of-semester assessments to monitor student progress and report to parents. The novelty of this study lies in its detailed documentation of a complete, phased management system for center-based learning within a specific Indonesian primary school context. Practically, these findings offer a replicable framework for other schools seeking to adopt or refine similar pedagogical models. The study contributes to educational literature by providing empirical evidence on the operational dynamics of center learning, demonstrating how structured management, diverse center types, and systematic evaluation collectively enhance the implementation of this approach in primary education.